Rancang Bangun Alat Pemanen Rumput Laut (Euchema cottoni) - Ibrahim, Ibrahim; Sukainah, Andi; Jamaluddin, Jamaluddin (Jurnal Pendidikan Teknologi Pertanian, 2024)
This research purpose to create a tool that can facilitate seaweed farmers in the process of harvesting other seaweed products. The working principle of the seaweed harvesting tool is to tie the seaweed rope bent to the roll on the harvester followed by rotating the roll connected to the pedal, when the roller is rotated, the stretch rope will pass through the separator between the rope and the seaweed, so that the seaweed is separated from the stretch rope. , by applying this working principle, it can make it easier for farmers who previously used the principle of working manually by pulling the rope without the help of any tools, after that the farmers also had to separate the seaweed that had been collected manually without the help of any tools so that it required more energy and time. long. This seaweed harvesting tool that was created can simplify and shorten the time for farmers in the harvesting process, as evidenced by the results of field research at the time of testing the tool, the results obtained are by conventional methods the average time used by farmers is 7 minutes 58 seconds while the results testing using a seaweed harvester using a roll diameter of 100 mm which is 5 minutes 28 seconds and by using a roll diameter of 50 mm which is 6 minutes 35 seconds. In terms of time efficiency of the seaweed harvester, a roll with a diameter of 100 mm is an efficient roll with an average time of 5 minutes 28 seconds.